Preventive treatment of coronavirus disease-2019 virus using coronavirus disease-2019-receptor-binding domain 1C aptamer by suppress the expression of angiotensin-converting enzyme 2 receptor - Noor S Hameed; Inam Sameh Arif; Basma Talib Al-Sudani (Wolters Kluwer Medknow Publications, 2023)
The cause of the worldwide coronavirus disease-2019 (COVID-19) pandemic is the severe acute respiratory syndrome coronavirus-2 (SARS-CoV-2). It is known to employ the same entry portal as SARS-CoV, which is the type 1 transmembrane angiotensin-converting enzyme 2 (ACE2) receptor. The receptor-binding domain (RBD) is located on the spike S-protein's S1 subunit of the spike glycoprotein. The most important and effective therapy method is inhibiting the interaction between the ACE2 receptor and the S-spike RBD. An aptamer is a small, single-chain oligonucleotide that binds strongly to the target molecule. Recently, a CoV-2-RBD-1C aptamer-based system with a 51-base hairpin structure was discovered to have substantial binding affinity against the SARS-CoV-2RBD with similar binding sites at ACE. In the current study, we will study the aptamer's effect as a SARS-CoV-2 spike blocker and inhibit its ACE2 receptors' binding by studying the toxicity of aptamer for this cell line by calcein assay and the inhibition test of CoV-2-RBD-1C aptamers on spike RBD-ACE2 binding. The results show the half-maximum inhibitory concentration of CoV-2-RBD-1C aptamer is 0.08188 μM. The inhibition effect of CoV-2-RBD-1C aptamer on spike RBD-ACE2 binding was determined at half-maximal effective concentration of 0.5 μM concentration. The percentage of spike-ACE2 binding inhibition in A549-hACE2 cells in the D614G variant after 30 s was 77%. This percentage is higher than D614 and N501Y and equals 55% and 65%, respectively, at 0.15 μM of CoV-2-RBD-1C aptamer. The CoV-2-RBD-1C aptamer prevents virus entrance through spike inhibition, which results in a 90% reduction in spike D614 virus transduction at 1.28 μM. In conclusion, the CoV-2-RBD-1C aptamer might be an effective treatment against COVID-19 infection because it directly affects the virus by blocking the S-spike of SARS-CoV-2 and preventing ACE2 receptor binding.